Case study of particulate matter emission from industrial sources in Teluk Kalung industrial estate, Kemaman, Terengganu - Muhammad Hisyam, Abdullah (2020)
The relationship between industrial development and increased levels of pollution is highly interconnected. Sustainable development planning will not only be able to generate a good economic environment but will also ensure a more comfortable and environmentally friendly life. High concentrations of particulate matter less than 10 micrometers (PM10) in the surrounding air can cause serious health effects on humans. One of the significant sources of PM10 emissions is from industrial activities. Meteorological factors also play an essential role in determining the level of concentration of air pollutants such as PM10. The main objective of this study is to develop a general guideline through modelling of the air dispersion for particulate matter (PM) from industrial emission sources at Teluk Kalung Industrial Estate. The specific objectives were: (i) to identify the characteristics of wind in the study area, (ii) to model the air dispersion for PM at the study area, and (iii) to compile an industrial planning and development guideline for the study area based on the modelling results. The wind speed and velocity at the study site were analyzed based on meteorological data obtained from the Air Quality Monitoring Station at Kampung Bukit Kuang, Kemaman, which is about 2 km from Teluk Kalung Industrial Estate. Meanwhile, air pollutant concentrations of particulate matter emitted from the industry had been derived from a chimney sampling report then modelled using the ISCST3 software supported by meteorological data such as wind speed, wind direction, ambient temperature and atmospheric stability. In addition, the particulate matter distribution value is plotted in the GIS application for visual visibility.The results of this study indicate that the annual wind direction blows more dominantly from the Northwest and Southeast directions. The comparison between the resultsof hourly particulate matter dispersion modelling with PM10 measurements demonstratesthat the production of particulate matter from the industry causes no signifi cant impact on the value of the measured PM10. The results of modelling of particulate matter on annual average concentration show that the highest concentration is 2.71 μg/m3while the average daily result is 21.21 μg/m3and both values exist in the industrial area. The isopleth analysis of both the annual and daily average modelling shows that industrial development can still be continued within the suggested border limits using a daily average value of 1 μg/m3. The main findings in this study especially the devised techniques, can contribute as a significant method for the determination of a vulnerable area as a result of a hazardous event of anthropogenic origin at microscale supported by local meteorological parameters. The devised method can be accustomized to other areas through localized meteorological parameters and serve as a guideline for the relevant authorities.